Online memes in Kenyan social media plat forms as a modality of negotiating gender-based violence in androcentric political contexts - Were, Marciana Nafula (Research Journal in Advanced Humanities, 2021)
This paper examines the re-production of images of gendered political bodies in digital scapes, and how these online forms participate in meaning-making of gender-based violence. The paper reads body images of (wo)men in politics, featured in online memes, as signs embodying society’s negotiation of gender-based violence in an androcentric political culture. It finds that both online and offline Kenyan political discourses generated by mainstream and subversive political discourses portray the female body as a subordinate category around which three notions of marginalisation are produced: the trivialised body, the violated body, and the sexualised body, all products of patriarchal and sexist biases. Online memes are of particular interest because they are means by which the current generation of young Kenyans engage in public discourses in ways that reflect ongoing popular discourses on gender in non-official publics.